Literature Review on Behavioral Bias in Financial Decision Making: Implications for Industrial Financial Management - muhamad irfan florid; henny sulistianingsih; heru aulia azman (Cita Konsultindo Research Center, 2024)
In this article, there are four main objectives; first, an introduction to behavioral biases in financial decision making; second, identifying the types of behavioral biases and their impact on decision making; third, the implications of behavioral biases in financial management (firm performance, financial strategy and risk management; fourth, strategies taken by managers to reduce the influence of behavioral biases in financial decision making. In the context of industrial financial management, a deep understanding of behavioral biases and their implications can assist companies in designing policies and strategies that minimize the negative impact of these biases. To answer the four objectives of the study that have been set, the study method used is descriptive qualitative research with literature analysis. The data source used in this study is secondary data in the form of articles obtained from Science Direct, emerald, Taylor & Francis, and Sage. The results of the literature review show four main findings. First, the introduction of behavioral biases in financial decision-making, investors' decisions are often not fully rational and are influenced by various psychological factors. This is in contrast to traditional finance theory which assumes that individuals act rationally and information is processed objectively. Second, there are 9 types of behavioral biases and 9 impacts on decision making. third, there are 5 implications of behavioral biases in financial management (company performance, financial strategy and risk management. Fourth, there are 10 strategies taken by managers to reduce the influence of behavioral biases in financial decision making.